Pola Komunikasi dalam Pengembangan Modal Manusia dan Sosial Pertanian - Retno Sri Hartati Mulyandari; Sumardjo Sumardjo; Nurmala K. Pandjaitan; Djuara P. Lubis (Forum penelitian Agro Ekonomi, 2010)
EnglishThis paper aims to analyze the high quality of agricultural human capital and social indicators in improving the performance of national development and to formulate their communication patterns to support capacity building of human and social capital of agriculture in every line of agricultural development. The lack of agricultural human capital and social capital capacity is one of the constraints causing the accessibility limitation for Indonesian agriculture to face the global competition. The low farmer’s education attainment has caused a low capacity of farmers to manage information and to adopt new technology resulting the low products quality. At the extension level, the shortage number and quality of the extension workers has also contributed to that situation. Beside low of basic capability, most of the extension workers do not have adequate mental capacity, especially related to integrity, communication skills, and moral and ethical capacity. At the policy maker’s level, many local government institutions have no capacity to mapping agricultural resources along with their capability to make use of the available resources. With the high technical ability, agricultural human resource as a capital resource and as a social resource should have shared values and rules that expressed through personal relationships, trust, and common sense about the community responsibilities. To strengthen agricultural sector In supporting national development, agricultural sector need appropriate communication patterns for agricultural human resource improvement at each level of agricultural development. Such communication pattern should be based on the convergent-interaction communication through knowledge sharing model. This model is appropriate for both agricultural personnel and for farmers. Through active role of various institutions within the Ministry of Agriculture and with the help of modern information technology, a network to reach farmers could be achieved. The extension workers or village facilitators are required in the development of agricultural community because of its important function as problem analyst, group supervisor, trainers, innovators, and liaison officers.IndonesianTulisan ini ditujukan untuk menganalisis indikator modal manusia dan sosial pertanian yang berkualitas dalam meningkatkan kinerja pembangunan nasional, dan merumuskan pola komunikasi untuk mendukung peningkatan kapasitas modal manusia dan sosial pertanian di setiap lini pembangunan pertanian. Keterbatasan kapasitas modal manusia dan sosial pertanian merupakan salah satu penyebab kurang mampunya pertanian Indonesia dalam menghadapi persaingan global. Rendahnya tingkat pendidikan petani menyebabkan kemampuan dalam mengolah informasi dan mengadopsi teknologi relatif sangat terbatas sehingga menghasilkan produk yang berkualitas rendah. Pada tingkat penyuluh, ketersediaannya di lapangan juga sangat terbatas jumlah dan kualitasnya. Selain kemampuan dasar yang masih rendah, sebagian besar penyuluh juga belum memiliki kapasitas mental yang memadai, khususnya terkait dengan integritas, kemampuannya dalam berkomunikasi, serta kapasitas moral dan etika. Sedangkan di tingkat pengambil kebijakan, masih banyak instansi daerah yang belum mampu memetakan sumber daya pertanian di daerah secara komprehensif dan memiliki kecermatan dalam membuat konsep pemanfaatannya. Selain memiliki kemampuan teknis yang tinggi, SDM pertanian sebagai modal manusia dan sosial pertanian juga harus memiliki dan berbagi nilai (shared values) serta pengorganisasian peran-peran (rules) yang diekspresikan dalam hubungan-hubungan personal (personal relationships), kepercayaan (trust), dan common sense tentang tanggung jawab komunitas (bersama). Agar sektor pertanian semakin kuat dalam mendukung pembangunan nasional, diperlukan pola komunikasi yang tepat untuk mendukung peningkatan kapasitas SDM pertanian di setiap lini pembangunan pertanian. Pola komunikasi dalam peningkatan kapasitas SDM pertanian dalam konsep sebagai modal manusia dan sosial yang unggul mengacu pada pola komunikasi interaksional konvergen melalui model berbagi pengetahuan (knowledge sharing model). Model ini tidak hanya sesuai untuk SDM dalam kategori aparatur pertanian, namun juga sesuai untuk petani. Peran aktif berbagai institusi dalam lingkup Departemen Pertanian yang diintegrasikan dengan perkembangan teknologi informasi, upaya untuk mewujudkan jaringan informasi bidang pertanian sampai di tingkat petani dapat diwujudkan. Fasilitator atau pendamping, khususnya penyuluh pertanian sangat dibutuhkan dalam pengembangan masyarakat karena mempunyai fungsi sebagai analis masalah, pembimbing kelompok, pelatih, inovator, dan penghubung.